2023
DOI: 10.17085/apm.22252
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of remimazolam–remifentanil and propofol–remifentanil during laparoscopic cholecystectomy

Abstract: Background: Remimazolam is a novel benzodiazepine with fast onset and short half-life. We compared the effects of remimazolam and propofol on recovery profiles for general anesthesia in patients undergoing laparoscopic cholecystectomy. Methods: We randomly assigned 108 patients to either a remimazolam (n=54) or propofol (n=54) group. Remimazolam and propofol were used for induction and maintanance of anesthesia. Following anesthesia, we recorded the time until an Aldrete score of 9 was achieved. The time to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Previous studies on remimazolam have reported that when flumazenil is administered postoperatively, the emergence time is shorter than that with traditional anesthetic drugs [41][42][43]. In the absence of flumazenil, the emergence time was not different or longer [44,45]. The results of the present study can also be attributed to the administration of flumazenil during the emergence phase.…”
Section: Discussionsupporting
confidence: 54%
“…Previous studies on remimazolam have reported that when flumazenil is administered postoperatively, the emergence time is shorter than that with traditional anesthetic drugs [41][42][43]. In the absence of flumazenil, the emergence time was not different or longer [44,45]. The results of the present study can also be attributed to the administration of flumazenil during the emergence phase.…”
Section: Discussionsupporting
confidence: 54%
“…[ 4 , 5 ] Fortunately, several emerging agents are being considered as acceptable alternatives, such as remimazolam, a new benzodiazepine for intravenous use in procedural sedation, has the rapid onset–offset properties comparable to propofol but with minor respiratory/circulatory depression. [ 6 , 7 ] Some studies have confirmed that remimazolam could be safely and effectively used for bronchoscopy and had a faster onset of action and faster recovery of neuropsychiatric functions compared to midazolam. [ 8 , 9 ] However, whether remimazolam may be the preferred pharmacological agents for bronchoscopy sedation in elderly patients has not been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, remimazolam has emerged as a safe option for continuous intravenous infusion and has been increasingly used as an anesthetic for sedation and general anesthesia. A few studies have compared postoperative recovery between remimazolam and propofol in general anesthesia, but these surgeries were relatively minor, and the results were inconsistent [6,7].…”
Section: Introductionmentioning
confidence: 99%